Antigen presentation by clonally diverse CXCR5+ B cells to CD4 and CD8 T cells is associated with durable response to immune checkpoint inhibitors - Ding, Lizhong; Sun, Lu; Bu, Melissa T.; Zhang, Yanjun; Scott, Lauren N.; Prins, Robert M.; Su, Maureen A.; Lechner, Melissa G.; Hugo, Willy (Frontiers in Immunology, 2023)
Introduction Increased T cell infiltration and interferon gamma (IFNγ) pathway activation are seen in tumors of melanoma patients who respond to ICI (immune checkpoint inhibitor) or MAPK pathway inhibitor (MAPKi) therapies. Yet, the rate of durable tumor control after ICI is almost twice that of MAPKi, suggesting that additional mechanisms may be present in patients responding to ICI therapy that are beneficial for anti-tumor immunity. Methods We used transcriptional analysis and clinical outcomes from patients treated with ICI or MAPKi therapies to delineate immune mechanisms driving tumor response. Results We discovered response to ICI is associated with CXCL13-driven recruitment of CXCR5+ B cells with significantly higher clonal diversity than MAPKi. Our in vitro data indicate that CXCL13 production was increased in human peripheral blood mononuclear cells by anti-PD1, but not MAPKi, treatment. Higher B cell infiltration and B cell receptor (BCR) diversity allows presentation of diverse tumor antigens by B cells, resulting in activation of follicular helper CD4 T cells (Tfh) and tumor reactive CD8 T cells after ICI therapy. Higher BCR diversity and IFNγ pathway score post-ICI are associated with significantly longer patient survival compared to those with either one or none. Conclusions Response to ICI, but not to MAPKi, depends on the recruitment of CXCR5+ B cells into the tumor microenvironment and their productive tumor antigen presentation to follicular helper and cytotoxic, tumor reactive T cells. Our study highlights the potential of CXCL13 and B cell based strategies to enhance the rate of durable response in melanoma patients treated with ICI.